Biomimetic pulsatile flows through flexible microfluidic conduits - M, Kiran Raj (Biomicrofluidics, 2019)
We bring out unique aspects of the pulsatile flow of a blood analog fluid (Xanthan gum solution) in a biomimetic microfluidic channel. Pressure waveforms that mimic biologically consistent pulsations are applied on physiologically relevant cylindrical microchannels fabricated using polydimethylsiloxane. The in vivo features of the relevant waveforms like peak amplitude and dicrotic notch are reproduced in vitro. The deformation profiles exhibit viscoelastic behavior toward the end of each cycle. Further, the time-varying velocity profiles are critically analyzed. The local hydrodynamics within the microchannel is found to be more significantly affected by pressure waveform rather than the actual wall deformation and the velocity profile. These results are likely to bear far-reaching implications for assessing micro-circulatory dynamics in lab on a chip based microfluidic platforms that to a large extent replicate physiologically relevant conditions.